Film Analysis as Society Analysis in Cultural Studies? (KULT_online, 2009)
The anthology Das Kino der Gesellschaft - die Gesellschaft des Kinos (The Cinema of Society - the Society of Cinema) opens up interdisciplinary perspectives on film analysis as society analysis. Most notably Cultural Studies, Psychoanalysis and Genre Theory are introduced as background for a sociological approach in the study of culture and are supported by case studies of single films and genres. The assembled contributions provide controversial, exciting lines of reasoning for current debates in film theory and the sociology of film, framed by theories of culture. Notwithstanding, the spatiality of cinema, possible situations of reception and the social differentiation of audiences is neglected at large. The collection provides fertile suggestions for continuative works in film theory by means of the heterogeneity of the contributions.